Two new species and four new records of Aquilegia (Ranunculaceae) from China - Erst, Andrey S.; Wang, Wei; Yu, Sheng-Xiang; Xiang, Kunli; Wang, Jian; Shaulo, Dmitry N.; Smirnov, Sergey V.; Kushunina, Maria; Sukhorukov, Alexander P.; Nobis, Marcin (Phytotaxa, 2017)
Two new species, Aquilegia xinjiangensis and A. hebeica from northern China, are here described and illustrated. Additionally four species, A. amurensis, A. flabellata, A. kamelinii and A. vicaria are recorded for the country for the first time. The identification key and diagnostic characters of all Aquilegia representatives from China including the newly described and recorded species are provided and discussed.